A testing and certification methodology for an open Ambient-Assisted Living ecosystem - João Pascoal Faria (2014)
To cope with the needs raised by the demographic changes in our society, several Ambient-Assisted Living (AAL) technologies have emerged in recent years, but those 'first offers' are often monolithic, incompatible and thus expensive and potentially not sustainable. The AAL4ALL project aims at improving that situation through the development of an open ecosystem of interoperable AAL components (products and services), tied together by an integration infrastructure, comprising a message-queue based service bus and gateways bridging the communication with devices. To that end, the project encompasses the specification of interfaces and requirements for interoperable components, against which candidates can be tested and certified before entering the ecosystem. This paper proposes a testing and certification methodology for such an ecosystem. Besides fulfilling specified pre-requisites, candidate components must pass unit tests that check their conformance with interface specifications and integration tests that check their semantic interoperability with other components in specified orchestration scenarios. Copyright (c) 2014, IGI Global.